Financing the Environment : Ukraine's Road to Effective Environmental Management - World Bank (Washington, DC, 2013)
This study presents a detailed analysis of the system of environmental expenditure in Ukraine with a particular focus on public expenditures. It examines the extent to which the present system meets national environmental objectives and identifies ways in which it can be improved and made more cost-effective. Since environmental spending is closely tied to sources of environmental revenues (partly a result of earmarking and partly because of the regulatory role that pollution charges and fines play), this review also covers revenue issues. The study is based on international systems of environmental accounting established by Organization for Economic Cooperation and Development (OECD).